2018
DOI: 10.2147/dddt.s159546
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinol ameliorates CCl<sub>4</sub>-induced liver fibrosis in rats through the regulation of Nrf2/HO-1 and NF-&kappa;B/I&kappa;B&alpha; signaling pathway

Abstract: Tanshinol, a water-soluble component isolated from Salvia miltiorrhiza Bunge, has a variety of biological activities involving anti-fibrotic effect. However, the exact role and the underlying mechanisms remain largely unclear. This study mainly focused on the anti-hepatic fibrotic activities and mechanisms of tanshinol on carbon tetrachloride (CCl4)-induced liver fibrosis in rats via anti-oxidative and anti-inflammation pathways. The rats were divided into 4 groups as follows: control, model, tanshinol 20 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 36 publications
9
21
0
Order By: Relevance
“…Taken together of tanshinol A‐changing phenotype (pathological observation, reduced MDA, and improvement in liver injury) and genotype (restorement in Aft4 , Fgf21 , Angplt4 and Vldlr ), hepatic injury alleviation, and hopylipidemic effect of tanshinol A are possibly associated with scavenge of triton‐1339W‐lead cellular stress through simultaneously mediating Vldlr transcriptional promotion and Aft4 ‐involved pathways. Therefore, a major mechanism of tanshinol A alleviating liver injury is partially consensus with previous research in terms of regulating Aft4 ‐involved pathway (Wang et al, ) and enhancing capacity of antioxidation (Yang et al, ), and it is first time that hopylipidemic mechanisms of tanshinol A are found to be highly associated with upregulation of Atf4/Fgf21/Vldlr . Still, there are some tanshinol A‐leading mRNA expression alteration such as Angptl4 and Fgf21 , which are fasting‐induced adipose factor (Gonzalez‐Muniesa et al, ) and pathogenesis of hepatic steatosis (Zarei et al, ), respectively, do not show consensus to previous research, and this inconsistency may be characteristic pathogenesis for triton‐1339W‐induced hyperlipidemia and liver injury, and it is reversible after tanshinol A treatment.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Taken together of tanshinol A‐changing phenotype (pathological observation, reduced MDA, and improvement in liver injury) and genotype (restorement in Aft4 , Fgf21 , Angplt4 and Vldlr ), hepatic injury alleviation, and hopylipidemic effect of tanshinol A are possibly associated with scavenge of triton‐1339W‐lead cellular stress through simultaneously mediating Vldlr transcriptional promotion and Aft4 ‐involved pathways. Therefore, a major mechanism of tanshinol A alleviating liver injury is partially consensus with previous research in terms of regulating Aft4 ‐involved pathway (Wang et al, ) and enhancing capacity of antioxidation (Yang et al, ), and it is first time that hopylipidemic mechanisms of tanshinol A are found to be highly associated with upregulation of Atf4/Fgf21/Vldlr . Still, there are some tanshinol A‐leading mRNA expression alteration such as Angptl4 and Fgf21 , which are fasting‐induced adipose factor (Gonzalez‐Muniesa et al, ) and pathogenesis of hepatic steatosis (Zarei et al, ), respectively, do not show consensus to previous research, and this inconsistency may be characteristic pathogenesis for triton‐1339W‐induced hyperlipidemia and liver injury, and it is reversible after tanshinol A treatment.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, it possesses multiply pharmacological functions i.e. protecting hepatocyte toward CCl 4 ‐induced liver injury (Wang et al, ), protecting endothelial cells against homocysteine‐induced injury (Chen et al, ; Song et al, ), and lowering methionine‐induced hyperhomocysteinemia (Tian et al, ) in rats. An increasing body of evidence shows that tanshinol A can improve health by mediating endogenous metabolism such as lipid metabolism, and thereby therapeutic effect and regulative mechanism of tanshinol A treating hyperlipidemia is worth further exploring.…”
Section: Introductionmentioning
confidence: 99%
“…(Lamiaceae; Y. Yang et al, ). Previous studies demonstrated that TAN exerted anti‐inflammatory and protective effects on vascular dementia and liver fibrosis (Wang et al, ; Y. Yang et al, ). In consistent with the previous studies, we revealed that TAN treatment alleviated the LPS‐induced HaCaT cell viability loss, apoptosis, and up‐regulation of Cox‐2 and iNOS expression, which indicated that TAN also could exert anti‐inflammatory and protective effects on pressure ulcers.…”
Section: Discussionmentioning
confidence: 96%
“…In terms of anti‐inflammatory activity, Y. Yang et al () reported that TAN inhibited inflammatory response in a rat model of vascular dementia. Wang, Wang, Song, Li, and Yuan () pointed out that TAN ameliorated carbon tetrachloride (CCl 4 )‐induced up‐regulation of transforming growth factor‐β, tumor necrosis factor‐α, cyclooxygenase 2 (Cox‐2), interleukin‐1β (IL‐1β), and IL‐6 expression in the serum of rats. However, there is no any information available about the effects of TAN on skin keratinocytes inflammatory injury in pressure ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is frequently used in herbal medicine for its anti-inflammatory activity, anti-arthritic properties, wound and burn healing capabilities, and anti-bacterial/anti-cancer properties 1115. There are several biologically active constituents in S. miltiorrhiza , including tanshinol 1618. Previous investigation has demonstrated that tanshinol regulates adhesion molecule expression of tumor necrosis factor alpha (TNF-α)-induced endothelial cells by blocking activation of nuclear factor kappa B (NF-κB) 19.…”
Section: Introductionmentioning
confidence: 99%